LASERS : Ti : sapphire laser synchronised with femtosecond Yb pump laser via nonlinear pulse coupling in Ti : sapphire active medium. (30th January 2017) - Didenko, N V; Konyashchenko, A V; Konyashchenko, D A; Kostryukov, P V; Kuritsyn, I I; Lutsenko, A P; Mavritskiy, A O
Abstract: A laser system utilising the method of synchronous pumping of a Ti : sapphire laser by a high-power femtosecond Yb 3+ -doped laser is described. The pulse repetition rate of the Ti : sapphire laser is successfully locked to the repetition rate of the Yb laser for more than 6 hours without the use of any additional electronics. The measured timing jitter is shown to be less than 1 fs. A simple qualitative model addressing the synchronisation mechanism utilising the cross-phase modulation of oscillation and pump pulses within a Ti : sapphire active medium is proposed. Output parameters of the Ti : sapphire laser as functions of its cavity length are discussed in terms of this model.